Evaluation for Irrigation Water Purposes of Groundwater Quality in the Vicinity of Sivas City Centre (Turkey) by Using Gis and an Irrigation Water Quality Index - Karakuş, Can Bülent; Yıldız, Sayiter (Irrigation and drainage, 2020)
In this study, the physical and chemical characteristics of wet and dry season groundwater quality parameters of 35 wells within the provincial boundaries of Sivas were used for calculations such as sodium adsorption ratio (SAR), Kelly's ratio (KR), sodium percentage (Na%), permeability index (PI), residual sodium carbonate (RSC) and magnesium hazard (MH), which are used in irrigation water quality ratings. Also, the irrigation water quality index (IWQI) was calculated for all groundwater sources within the study area. Groundwater quality parameters and the spatial distribution of the parameters calculated throughout the study were mapped using GIS, and irrigation water quality evaluation was performed in accordance with USA Salinity Laboratory diagram and irrigation water quality standards. The correlations between the irrigation water quality parameters were determined using Pearson correlation analysis. IWQI values showed that the majority of groundwater samples (45.7%) are in the ‘weak' (MR: medium rating) category for the dry season, whereas 42.9% of groundwater samples fall within the ‘very weak' (HR: high restriction) category for the wet season. © 2019 John Wiley & Sons, Ltd. Résumé Dans cette étude, les caractéristiques physiques et chimiques des paramètres de qualité de la nappe phréatique en saison sèche et humide de 35 puits situés à l'intérieur des limites provinciales de Sivas ont été utilisées pour des calculs tels que le rapport d'adsorption sodique (SAR), le rapport de Kelly (KR), le pourcentage de sodium (Na%), indice de perméabilité (PI), carbonate de sodium résiduel (RSC) et risque de magnésium (MH), utilisés comme indicateurs de qualité de l'eau d'irrigation. De plus, l'indice de qualité de l'eau d'irrigation (IWQI) a été calculé pour toutes les sources d'eau souterraine de la zone d'étude. Les paramètres de qualité de l'eau souterraine et la distribution spatiale des paramètres calculés tout au long de l'étude ont été cartographiés à l'aide d'un système d'information géographique (SIG). L'évaluation de la qualité de l'eau d'irrigation a été réalisée conformément au diagramme américain de Salinity Laboratory et aux normes de qualité de l'eau d'irrigation. Les corrélations entre les paramètres de qualité de l'eau d'irrigation ont été déterminées à l'aide de l'analyse de corrélation de Pearson. Les valeurs IWQI ont montré que la majorité des échantillons d'eaux souterraines (45.7%) sont représentés par la catégorie ‘faible' (MR: classement moyen) pour la saison sèche, alors que 42.9% des échantillons d'eau souterraine appartiennent à la catégorie ‘très faible' (HR: restriction élevée) pour la saison des pluies. © 2019 John Wiley & Sons, Ltd.